ANALYSIS OF FIGURATIVE LANGUAGE IN CHARLIE PUTH’S SONG ON CHARLIE ALBUM - umar, Meis sintia; Husain, Dahlia (LPPM STISIPOL Mujahiddin, 2024)
This research aims to analyzing the figurative language find in Charlie puth's song on Charlie album. This research uses descriptive qualitative method and used the theory of Knickerbocker and Renninger in analyzing the figurative language in Charlie Puth‟s song. The researcher find 39 data deals with types of figurative language: Simile 5 data, Metaphor 3 data, Personification 4 data, Synecdoche 3 data, Metonymy 8 data, Hyperbole 11 data, Irony 4 data, and Paradox 1 data. Through this research, the researcher found out that in Charlie Puth's songs on Charlie's album, he uses a lot of hyperbole figurative language because he expresses his feelings excessively through song lyrics.